NILAI MORAL DALAM DWILOGI NOVEL SAMAN DAN LARUNG KARYA AYU UTAMI - Muplihun, Endra; Priyadi, A. Totok; Syam, Christanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractSaman and Larung are novels that tell about history and politics. There are a lot of moral values that can be learned. Thus, the writer wants to explore the values contain in the novels. The writer uses descriptive method, qualitative research, and sociological literature approach. The sources used in this research are novels by Ayu Utami Saman and Larung. The data obtained are words, sentences, and texts that have moral values. Reading and taking notes are used as data gathering method by presenting character and characterization of the main character. Data reliability is tested by checking references, peer reading and discussion, and triangulation. Based on the data analysis, there are three conclusions. They are (1) value of fear of God. (2) honesty, friendship, helpful, respect others, and respect government. (3) self-control, fear of sins, modesty, confession, self-esteem, just, and careful. Key word: moral values, Saman and Larung by Ayu Utami